WHO 2016 classification: changes and advancements in the diagnosis of miscellaneous primary CNS tumours - Sahm, Felix; Reuss, David; Giannini, Caterina (Neuropathology & applied neurobiology, 2018)
This short review highlights significant changes and recent findings incorporated to varying extent in the WHO 2016 definition of a variety of tumours, including peripheral nerve sheath tumours, meningiomas, mesenchymal nonmeningothelial tumours, melanocytic tumours, lymphomas and histiocytic tumours, germ cell tumours and non-neuroendocrine pituitary tumours. Most notable classification changes include: adding ‘hybrid nerve sheath tumours’ to the spectrum of benign nerve sheath tumours; an updated definition of atypical meningioma (WHO grade II), including cases with brain invasion; recognizing dural solitary fibrous tumour (SFT) and haemangiopericytoma (HPC) as a single tumour entity characterized by NAB2 and STAT6 gene fusions for which the term SFT/HPC was chosen; recognizing that pituitary granular cell tumour, spindle cell oncocytoma, and pituicytoma all share nuclear expression of TTF-1, possibly representing a spectrum of a single nosological entity derived from posterior pituitary glial cells. The most significant diagnostic markers which have emerged include: inactivation of NF1, CDKN2A, and PRC2 components, SUZ12 and EED in MPNST, leading to neurofibromin and H3K27me3 expression loss; GNAQ and GNA11 mutations in CNS primary melanocytic tumours; BRAFV600E mutation in histiocytic tumours (Langerhans cell histiocytosis and Erdheim-Chester disease) and papillary craniopharyngioma, which provides both a diagnostic marker in the appropriate pathological setting and a therapeutic target. The WHO 2016 Classification has balanced cutting-edge knowledge on the molecular characteristics of the miscellaneous CNS tumours reviewed here with a practical approach for their daily diagnostic work-up. Much more progress can be expected in the classification of these neoplasms in the near future.